2013
DOI: 10.3758/s13421-013-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Memory for child sexual abuse information: Simulated memory error and individual differences

Abstract: Building on the simulated-amnesia work of Christianson and Bylin (Applied Cognitive Psychology, 13, 495-511, 1999), the present research introduces a new paradigm for the scientific study of memory of childhood sexual abuse information. In Session 1, participants mentally took the part of an abuse victim as they read an account of the sexual assault of a 7-year-old. After reading the narrative, participants were randomly assigned to one of four experimental conditions: They (1) rehearsed the story truthfully (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 45 publications
6
50
2
Order By: Relevance
“…Of more interest, we found that participants were most likely to falsely deny that they discussed several details with an experimenter when they were instructed to deny experienced details a week before. Our experiment is the first showing the adverse effects of false denials on the reporting of information (but see McWilliams et al, 2014 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of more interest, we found that participants were most likely to falsely deny that they discussed several details with an experimenter when they were instructed to deny experienced details a week before. Our experiment is the first showing the adverse effects of false denials on the reporting of information (but see McWilliams et al, 2014 …”
Section: Discussionmentioning
confidence: 99%
“…Because rehearsal strengthens long-term memory performance (e.g., Dark & Loftus, 1976), a lack of rehearsal might perpetuate impoverished memories for facets of the event. Furthermore, false denials might also lead to "no think" executive control mechanisms which might lead to a False denials 11 reduction of unwanted memories entering consciousness (Anderson & Greene, 2001;McWilliams, Goodman, Lyons, Newton, & Avila-Mora, 2014). Second, false denials might affect source monitoring.…”
Section: The Present Studymentioning
confidence: 99%
“…In an expansion and replication of an earlier study, participants who minimized their own culpability during Session 1 made more commission errors during Session 2 (van Oorsouw & Giesbrecht, ). Research in our own laboratory, in which participants simulated memory impairment for committing a crime (Newton, Ghetti, & Goodman, ) or for CSA victimization (McWilliams et al, ; Newton et al , ), has largely confirmed the aforementioned pattern of results.…”
Section: Introductionmentioning
confidence: 99%
“…Other victims may greatly minimize what happened, asserting that the abuse was not serious. From a memory perspective, such omissions or minimizations can be considered a lack of rehearsal of what really occurred, which can negatively affect later recall (Ghetti et al , ; McWilliams, Goodman, Lyons, Newton, & Avila‐Mora, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation